The role of risk management and good governance to detect fraud financial reporting - Sunaryo, Kunti; Astuti, Sri; Zuhrohtun, Zuhrohtun (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2019)
The aim of this study is to investigate the organizational factors, auditor opinion and the role of internal auditor in banking industry to detect fraud in Indonesia. Observation data in this study are the years from 2013 to 2017. This study is an empirical study and the data are selected by using sampling technique. Observation data in this study are as many as 45, and are processed by using logistic regression analysis instrument. The dependent variable studied is fraud. Meanwhile, the corporate organizational factors are risk disclosure and independency of intern auditor function as well as independent auditor opinion. The testing result proofs that there is no corporate organizational variable and independent auditor opinion significantly affecting indication of fraud in banking company.